Penerapan Metode Pembelajaran Pesantren Tradisional dan Modern - Sabila, Halimatus; Astuti, Windi Dwi; Yuliarti, Risma; Husna, Difa’ul (Lembaga Yasin AlSys, 2024)
The background in this article is the application of traditional and modern Islamic boarding school learning methods. The purpose of writing this article is to explain the differences between modern and traditional Islamic boarding schools, explain the various learning methods in modern Islamic boarding schools and explain the advantages of the methods applied in both Islamic boarding schools. This article uses the library research method so that in this article the researcher takes data from literature related to this research. The data in this article is presented descriptively, namely a presentation in the form of writing that has been studied in depth. The results of this research explain the application of learning methods carried out in modern and traditional Islamic boarding schools. There is a need to develop learning models in Islamic boarding schools, namely by using better learning methods, namely using more effective methods in class, planning and implementing activities in such a way continuously and also through group work.